Reconstruction of the pre-compactional thickness of the Zechstein Main Dolomite in northwest Poland - Semyrka, Grażyna; Gancarz, Marzena; Mikołajewski, Zbigniew (Geologos, 2015)
Our reconstruction of the pre-compactional thickness of the Main Dolomite strata from the so-called Grotów Peninsula (northwest Poland) was based on macroscopic observations of drill cores from three wells: Mokrzec-1, Sieraków-4 and Międzychód-5. These wells are located in various palaeogeographical zones of the Main Dolomite and cored rocks represent a range of microfacies. The amount of compactional reduction in thickness of the Main Dolomite was estimated by summing the total heights (Wst) of all stylolites encountered in logs of these wells. For calculations, a generalised model of a drill core was developed, which embraced all types of stylolite seams present in the Main Dolomite succession studied. Also the method of stylolite dimensioning was demonstrated. The number of stylolites in the drill cores studied varied from 511 in the Sieraków-4 well to 1,534 in the Międzychód-5 well. In all cores studied low-amplitude macrostylolites predominated, but the reduction of thickness was controlled mostly by the low- and medium-amplitude macrostylolites. The largest number of stylolites was found in the grainstone/packstone microfacies. The turnout of stylolites depends of microfacies. The highest density of stylolites was documented in mudstones/wackestones (24 stylolites per metre of rock thickness) and the lowest in boundstones (14 stylolites per metre of rock thickness). The low-amplitude stylolites appear most frequently in the mudstone/wackestone microfacies (15 stylolites per metre of rock thickness); in grainstones/packstones, rudstones/floatstones and boundstones middle-amplitude stylolites are rare (3 stylolites per metre of rock thickness). The degree of compaction of the Main Dolomite succession studied varied from 6 to 10%; hence, its calculated initial thickness also varied in the wells studied: from 41.3 m in the Sieraków-4 well to 56.9 m in the Mokrzec-1 well and to 97.1 m in the Międzychód-5 well. The volumes of reservoir fluids expelled during compaction of 1 m3 of Main Dolomite carbonates were estimated as 56 l in the Sieraków-4 well, 90 l in the Mokrzec-1 well and 97 l in the Międzychód-5 well.